Analisis Quality Of Service (QoS) Jaringan Internet Pelanggan Pada ISP Jalurdata.Net Menggunakan Metode Hierarchical Token Bucket (HTB) dan Per Connection Queue (PCQ) - AWALIYANI, IKNA; Abdul Aziz, RZ (Institut Teknologi Garut, 2024)
Problems regarding bandwidth continuity on an internet network often occur due to the lack of maximum utilization of Quality of Service. Without bandwidth management, problems will occur on a network. Quality of Service is the right way to allocate bandwidth in a network because it not only limits bandwidth but also maintains even and stable bandwidth quality. In this study, the methods used are the Hierarchical Token Bucket (HTB) and Per Connection Queue (PCQ) methods by calculating parameters such as Throughput, Delay, Jitter, and Packet loss. The benefit of this research is to compare the two bandwidth management methods and find the most effective method to implement in an ISP. The final comparison of QoS values using the HTB and PCQ methods based on the parameter index values is the same, but after comparing based on the actual parameter values, the PCQ (Peer Connection Queue) method shows superior performance with a higher throughput value of 84%, lower jitter at 13.0948%, and lower packet loss at 0.03%. Although HTB has lower delay at 76.758 ms, the PCQ method is more significant in network scenarios, particularly for stability and consistency in data transmission.